High Hydrogen Permeance Silica Membranes Prepared by a Chemical Vapor Deposition Method - Ikeda, Ayumi; Ono, Ryuhei; Nomura, Mikihiro (Journal of Membrane and Separation Technology, 2015)
H2 permselective silica hybrid membranes were successfully prepared by using a counter diffusion chemical vapor deposition (CVD) method. Hexyltrimethoxysilane (HTMOS), phenyltrimethoxysilane (PhTMOS) or diphenyldimethoxysilane (DPhDMOS) were used as silica precursors. The oxidants were O3 or O2. These reactants were provided at the opposite side of the γ-alumina substrates, and the deposition occurred in the pores of the substrates. The HTMOS/O3 derived membrane deposited at 450°C showed the highest H2 permselectivity. The H2 permeace was 2.1×10-6 mol m-2 s-1 Pa-1 with the H2/SF6 permeance ratio of 5.9×106. H2 permeances through the HTMOS derived membranes increased with increasing the deposition temperatures. While the H2 permeance through the PhTMOS and DPhDMOS derived membranes decreased with increasing the deposition temperatures. The PhTMOS derived membrane prepared at 150°C showed the H2 permeance of 1.7×10-6 mol m-2 s-1 Pa-1 with the H2/SF6 permeance ratio of 13. The PhTMOS membrane prepared at 320°C showed the highest H2/SF6 permeance ratio of 1.8×104among the PhTMOS derived membranes. However, the H2/SF6 permeance ratio through the DPhDMOS membranes showed the different trend. Higher H2/SF6 permeance ratio was found through the DPhDMOS derived membranes deposited at 180°C and 360°C. The maximum H2/SF6 permeance ratio was 4.2×104 through the DPhDMOS membrane deposited at 180°C. The decomposition properties of organic groups on silica surface are investigated by using hydrolysis powders derived from the each silica precursor. The HTMOS powders showed O3 stability after the high temperature treatment. Thus, high H2 permselective membranes were prepared by the HTMOS at 450 °C.